2015
DOI: 10.1007/s12185-015-1844-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive properties of Wharton’s jelly-derived mesenchymal stromal cells in vitro

Abstract: Recent studies have reported that mesenchymal stromal cells (MSCs) migrate to areas of inflammation and suppress adverse immune reactions. Bone marrow (BM)-derived MSCs have been successfully used in patients with acute graft versus host disease (GVHD), but the harvesting of BM carries certain risks for the donor. To circumvent these, we obtained MSCs from Wharton's jelly (WJ) derived from umbilical cord and investigated their potential for immunosuppression. In a mixed lymphocyte reaction (MLR), responder T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 24 publications
3
19
0
Order By: Relevance
“…The effectiveness of UCMSC therapy can also be explained by their immunomodulatory properties. In vitro experiments have shown that UCMSCs, as well as MSCs isolated from bone marrow and adipose tissue, possess the ability to reduce the expression of proinflammatory cytokines by immune cells [47][48][49] and to inhibit the proliferation of activated T lymphocytes [50][51][52]. They also suppress the differentiation and maturation of dendritic cells [53,54] and mediate the induction of a regulatory phenotype in activated T lymphocytes (Treg) [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of UCMSC therapy can also be explained by their immunomodulatory properties. In vitro experiments have shown that UCMSCs, as well as MSCs isolated from bone marrow and adipose tissue, possess the ability to reduce the expression of proinflammatory cytokines by immune cells [47][48][49] and to inhibit the proliferation of activated T lymphocytes [50][51][52]. They also suppress the differentiation and maturation of dendritic cells [53,54] and mediate the induction of a regulatory phenotype in activated T lymphocytes (Treg) [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…However, an explant culture system provides a more physiologic milieu to harvest intact cells compared with enzymatic isolation. 51 UC-MSCs are positive for CD73, CD90, CD105, and human leukocyte antigen (HLA) class I and negative for CD45 and HLA-DR. 36,52 They display immunosuppressive potential by cell-cell contact with activated T cells, 53 and they efficiently suppress the proliferation and cytokine production of a subset of circulating T cells. 54 Moreover, UC-MSCs produce large amounts of tolerogenic IL-6, transforming growth factor (TGF)-β, and VEGF-1.…”
Section: Umbilical Cordmentioning
confidence: 99%
“…Absence of signifi cant stimulation of allogeneic lymphocytes by different type of MSCs has been documented [6]. MSC from different sources; Bone Marrow (BM) [7], Placenta (PL-MSC) [8], Umbilical Cord (UC-MSC) [6], Wharton's Jelly (WJ-MSC) [9], Umbilical Cord Lining (CL-MSCs) and Cord Blood (CB-MSCs) [10], Amniotic Membrane (AM-MSC) [6,11], tonsil [12], cornea [13] and Liver [14], Adipose Tissue (AT-MSC) [15], exert their immunomodulatory effect on immune cells. This could confi rm the universal inhibitory effect of MSCs despite their origins or culture environment.…”
Section: Effect Of Origins and Type Of Msc On Magnitude Of Inhibitorymentioning
confidence: 99%